(untitled) - Le Cozannet, Gonéri; Thiéblemont, Rémi; Rohmer, Jeremy; Capderrey, Cécile (Comptes Rendus. Géoscience, 2025)
As part of its third national adaptation plan to climate change, France is developing new scenarios approximately aligned with the current commitments of states to reduce their greenhouse gas emissions and anticipating 3 °C of global warming by 2100. Here, we present sea-level projections aligned with this assumption. New methodological developments include a statistical treatment to ensure the continuity of trends and uncertainties before and after 2100. Our results show that there is a probability of approximately 50% that the sea-level rise guidance of 60 cm—used for coastal risk prevention in France—will be exceeded by 2100 at 3 °C global warming levels (GWL). This no longer provides safety margins expected in 2011 based on the 4th Assessment Report of the IPCC, suggesting an update is now needed. The sea-level scenarios presented here might support the 3rd National Adaptation Plan, published in March 2025. While the publication of the plan was generally welcomed, concerns were raised regarding the lack of specific adaptation objectives in coastal areas and uncertainties regarding the potential use and enforcement of the new climate change scenario. We argue that an open debate on the political choices involved in coastal adaptation would build an opportunity to create more resilient coastal zones for the benefits of human communities and for economic activities and coastal ecosystems.